Detection of sdhB Gene Mutations in SDHI-Resistant Isolates of Botrytis cinerea Using High Resolution Melting (HRM) Analysis - Samaras, Anastasios; Madesis, Panagiotis; Karaoglanidis, George S. (Frontiers in Microbiology, 2016)
Botrytis cinerea, is a high-risk pathogen for fungicide resistance development. Pathogen` resistance to SDHIs is associated with several mutations in sdh gene. The diversity of mutations and their differential effect on cross-resistance patterns among SDHIs and the fitness of resistant strains necessitate the availability of a tool for their rapid identification. This study was initiated to develop and validate a high-resolution melting (HRM) analysis for the identification of P225H/F/L//T, N230I and H272L/R/Y mutations. Based on the sequence of sdhB subunit of resistant and sensitive isolates, a universal primer pair was designed. The specificity of the HRM analysis primers was verified to ensure against the cross-reaction with other fungal species and its sensitivity was evaluated using concentrations of known amounts of mutant`s DNA. The melting curve analysis generated nine distinct curve profiles, enabling the discrimination of all the 4 mutations located at codon 225, the N230I mutation, the 3 mutations located in codon 272 and the non mutated isolates (isolates of wild type sensitivity). Similar results were obtained when DNA was extracted directly from artificially inoculated strawberry fruit. The method was validated by monitoring the presence of sdhB mutations in samples of naturally infected strawberry fruits and stone fruit rootstock seedling plants showing damping off symptoms. HRM analysis data were compared with a standard PIRA-PCR technique and an absolute agreement was observed suggesting that in both populations the H272R mutation was the predominant one, while H272Y, N230I and P225H were detected in lower frequencies. The results of the study suggest that HRM analysis can be a useful tool for sensate, accurate and rapid identification of several sdhB mutations in B. cinerea and it is expected to contribute in routine fungicide resistance monitoring or assessments of the effectiveness of antiresistance strategies implemented in crops heavily treated with botryticides.